A Study Of Appreciation In Football Commentaries In English And Vietnamese - Trần Hữu Thuần (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis explored the use of Appreciation in football commentaries in English and Vietnamese. The study focuses on Appreciation in the category of Attitude, one of the three subsystems within the Appraisal theory. This descriptive quantitative and qualitative study was conducted based on a descriptive framework of functional grammar, appraisal and speech acts theory. The data were extracted from football commentary articles and transcripts on websites. 150 English samples and 150 Vietnamese ones in football commentaries such as adjective phrases, noun phrases, clauses and sentences were collected in news, newspaper, and live commentary on website. The study examined the syntactic and semantic features of Appreciation in football commentaries in English and Vietnamese. In syntactic aspect, the data were examined in view of clause as message and nominal group in functional grammar. In semantic aspect, the data were analyzed in view of appraisal and speech acts theory. Based on the result of data analysis, some implications and suggestions comprehending and using appreciation in football commentaries effectively were given to Vietnamese students of English and those who are interested in the appraisal of football commentaries.